Myasthenia gravis in pregnancy: a rare disorder with multidisciplinary management - Varun, Neha; Kumari, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Myasthenia gravis is a rare autoimmune disorder characterized by nicotinic acetylcholine receptor autoantibodies, affecting the neuromuscular transmission leading to progressive weakness. As this disease is seen in the reproductive age group, clinicians need to be aware of this condition and its multidisciplinary management which is the key to successful outcome. Myasthenia gravis especially when associated with pregnancy is a high-risk condition, that may affect both the mother and the fetus and may result in adverse outcome. The pregnancy course is unpredictable with MG.